Implementasi Kurikulum Merdeka Pada Pendidikan Inklusi di SD Al-Azhar Medan - Sarah Dina; Muhammad Firdaus; Nisfu Kurniyatillah (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2024)
This study aims to find out how the implementation of the self-learning curriculum is carried out, to find out what are the obstacles and challenges faced in implementing the self-learning curriculum, to analyze how the concept of inclusive education is implemented, and to find out how the implementation and evaluation of inclusive education forms of the independent curriculum in elementary schools. Al-Azhar Medan. This study used a field study method with a descriptive qualitative research type of analysis. The research data consists of primary data and secondary data. The primary data of this research are books that contain inclusive education. While the secondary data of this research is in the form of articles, journals, government regulations, scientific papers and so on. The data collection carried out by the author in this study was by observing, interviewing and documenting. The results obtained from this study are: (1) the implementation of the independent learning curriculum initiated by the government, (2) the implementation of inclusive education at SD Al-Azhar Medan which starts from curriculum planning in the RPPM and RPPH which is based on curriculum modification by adjusting on the needs and abilities of students which include moral, social, creative, language, and skills values, (3) the process of assessing inclusive education at SD Al-Azhar Medan is carried out by the teacher and the results of therapy.